Rescue levodopa‐carbidopa intestinal gel (LCIG) therapy in Parkinson's disease patients with suboptimal response to deep brain stimulation. Issue 10 (13th September 2019) - Elkouzi, Ahmad; Ramirez‐Zamora, Adolfo; Zeilman, Pam; Barabas, Matthew; Eisinger, Robert S.; Malaty, Irene A.; Okun, Michael S.; Almeida, Leonardo
Abstract: Objective: To evaluate the effectiveness of levodopa‐carbidopa intestinal gel (LCIG) as an add‐on rescue therapy following deep brain stimulation (DBS) for treatment of motor fluctuations. Background: Both DBS and LCIG are FDA‐approved therapies for treatment of motor fluctuations in advanced PD. Few studies have examined dual therapy for refractory motor fluctuations and it is unknown what the effect on quality of life will be in advanced PD. Methods: We conducted a retrospective study using a large database of all medical and surgical PD cases at the University of Florida. Six patients were identified with DBS who subsequently received rescue LCIG therapy. The clinical histories, indications for intervention and outcomes were reviewed. Results: All patients were managed initially with DBS (bilateral STN DBS ( n  = 3), bilateral GPi DBS ( n  = 1), unilateral GPI DBS ( n  = 2)). Patients with well‐placed ( n  = 3) and suboptimally placed DBS leads ( n  = 3) had significant reduction in their motor fluctuations with improvement in the off‐medication time after rescue LCIG therapy. Improvement in quality of life scores (PDQ‐39) was appreciated in four DBS patients following the addition of LCIG therapy. Conclusions: LCIG is a promising add‐on rescue therapy for select patients with existing DBS devices. The LCIG may possibly reduce motor fluctuations and improve quality of life in advanced PD irrespective of the DBS target or the accuracy of lead placement. Dual therapy may also be ideal for patients who are considered high risk for additional DBS surgeries.